Ozone in Nature and Practice (IntechOpen, 2018)
Ozone has an important and irreplaceable function in nature and human society. It preserves life on the Earth by stratospheric ozone layer. On the other hand, the formation of ground-level ozone by reactions of hydrocarbons with nitrogen dioxide in the presence of sunlight has adverse effects on humans and animals as well as on various materials. This book concentrates on the protection of stratospheric ozone and prevention of ground-level ozone formation; applications of its strong oxidizing properties in the treatment of water, wastewater and sludge; odor and color removal; uses in medicine as a disinfectant; and various other ozone therapies. It also deals with catalytic ozonation in water treatment, control methods for ozone applications on biological systems, various areas of ozone use in dental care, follow-up therapy and prevention.